2021
DOI: 10.1001/jamanetworkopen.2021.10789
|View full text |Cite
|
Sign up to set email alerts
|

Variation in SARS-CoV-2 Infection Risk and Socioeconomic Disadvantage Among a Mayan-Latinx Population in Oakland, California

Abstract: US Latinx populations are disproportionally affected by the SARS-CoV-2 pandemic, with higher rates of infection and associated morbidity and mortality. 1 Although often treated as homogeneous, members of Latinx communities vary by national origin, immigration status, and language. 2 Oakland, California, is home to many Latinx individuals and an estimated 10 000 Mayan individuals, many of whom speak Indigenous languages. 3 Early in the pandemic, community-based organizations (CBOs) in Oakland, California, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…They are also more likely to have chronic conditions associated with increased risk of developing severe COVID-19 infection compared with non-Latinx White individuals. 7 , 8 , 9…”
Section: Introductionmentioning
confidence: 99%
“…They are also more likely to have chronic conditions associated with increased risk of developing severe COVID-19 infection compared with non-Latinx White individuals. 7 , 8 , 9…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we assumed that the socio-demographic characteristics we included in the model were reflective of risk. Several of the predictors included in the model have empirically been shown to be associated with higher rates of infection, including being LatinX and having low income [ 25 , 30 , 38 , 39 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence estimates have varied widely, however, due to differences in sampling approaches, the target population, and the dates during which surveys were implemented [ 18 , 24 ]. In addition, general population estimates may not take into account the higher rates of infection among subgroups; for example, several studies have demonstrated that Latinx communities in the U.S. are more highly affected by the pandemic, likely due to occupational hazard, higher housing density and other factors [25] , [26] , [27] , [28] , [29] , [30] . Errors in prevalence estimates can also occur because of imperfect antibody test performance, which can under- or overestimate actual infections [ 24 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“… 69 Socioeconomic deprivation has repeatedly been shown to be associated with increased risk for infection, likely because it is associated with increased probability of more frequent and higher risk exposures. 70 , 71 , 72 , 73 , 74 …”
Section: Determinants Of Infectiousnessmentioning
confidence: 99%